GEE Estimation of a Two-Equation Panel Data Model: An Analysis of Wage Dynamics and the Incidence of Profit-Sharing in West Germany - Markus Pannenberg; Martin Spiess (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
We propose a generalized estimating equations approach to the analysis of the mean and the covariance structure of a bivariate time series process of panel data with mixed continuous and discrete dependent variables. The approach is used to jointly analyze wage dynamics and the incidence of profit-sharing in West Germany. Our findings reveal a significantly positive conditional correlation of wages and the incidence of profit-sharing. Furthermore, they indicate that permanent unobserved individual ability is comparatively more important in the profit-sharing than in the wage equation and show that shocks have a long-lasting effect on transitory wages but not on the incidence of profit-sharing. Hence, the results support theoretical predictions that selection into profit-sharing is mostly due to unobservable ability and that profit-sharing ties wages more closely to productivity.
Keywords: J33; J31; C35; C33; D31; 330; generalized estimating equations; covariance structure; longitudinal data; real wages; variable pay; Zeitreihenanalyse; Panel; Varianzanalyse; Reallohn; Erfolgsbeteiligung; Schätzung; Deutschland